Sorting and magnetic-based isolation of reticulated platelets from peripheral blood - Bernlochner, Isabell; Klug, Melissa; Larasati, Ditya; Von Scheidt, Moritz; Santovito, Donato; Hristov, Michael; Weber, Christian; Laugwitz, Karl-Ludwig; Bongiovanni, Dario (Platelets, 2021)
Reticulated Platelets (RPs) are large, RNA-rich, prothrombotic and hyperactive platelets known to be elevated in high-risk populations such as diabetics and patients with acute coronary syndrome. High levels of RPs correlate with mortality and adverse cardiovascular events in patients with coronary artery disease as well as with an insufficient antiplatelet response to thienopyridines and aspirin after percutaneous coronary interventions, making them an appealing drug target. However, processing of platelets is challenging and no specific marker for RPs exists. Until now, the gold standard laboratory-based method to study them is based on the flow cytometric measurement of their cell size and their RNA-content with the fluorescent dye Thiazole Orange (TO). Nevertheless, standardized protocols for staining and processing of RPs are missing and the existing techniques were not applied for cell sorting. We provide here a structured and reproducible method to detect, isolate and collect RPs from peripheral blood by RNA-specific staining with TO implementing several platelet inhibitors as well as magnetic labeling allowing sufficient cell recovery and deep biological investigation of these platelets.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Immature platelets; platelet isolation; reticulated platelets